The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1017/s0007114511006945
|View full text |Cite
|
Sign up to set email alerts
|

Multi-micronutrient-fortified biscuits decreased the prevalence of anaemia and improved iron status, whereas weekly iron supplementation only improved iron status in Vietnamese school children

Abstract: In Vietnam, nutrition interventions do not target school children despite a high prevalence of micronutrient deficiencies. The present randomised, placebo-controlled study evaluated the impact of providing school children (n 403) with daily multiple micronutrient-fortified biscuits (FB) or a weekly Fe supplement (SUP) on anaemia and Fe deficiency. Micronutrient status was assessed by concentrations of Hb, and plasma ferritin (PF), transferrin receptor (TfR), Zn and retinol. After 6 months of intervention, chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The authors found that the use of the fortified complementary food for 6 months resulted in a significant increase in mean hemoglobin levels and that it had a higher compliance than the use of sprinkles [40]. These findings have been supported by a number of other studies, indicating the advantages of using fortified foods over micronutrient supplements, particularly for infants and young children [41,42]. …”
Section: Food Fortification As a Tool For Addressing Micronutrient Dementioning
confidence: 89%
“…The authors found that the use of the fortified complementary food for 6 months resulted in a significant increase in mean hemoglobin levels and that it had a higher compliance than the use of sprinkles [40]. These findings have been supported by a number of other studies, indicating the advantages of using fortified foods over micronutrient supplements, particularly for infants and young children [41,42]. …”
Section: Food Fortification As a Tool For Addressing Micronutrient Dementioning
confidence: 89%
“…The impact of school feeding on micronutrient status may depend on the dose, initial micronutrient status, and interactions with other micronutrients supplemented. The iron status of Kenyan schoolchildren was associated with the dosage of iron-fortified flour (Andang'o and others 2007), while a randomized controlled trial in Vietnam showed that only multifortified biscuits reduced anemia more than iron supplementation, which suggests that other micronutrients affect anemia status (Hieu and others 2012).…”
Section: Nutrient Adequacymentioning
confidence: 99%
“…Similarly, Chagan et al 34 performed a long-term controlled randomized double blind study in 6 to 24-month-old children in the rural area of South Africa and showed that supplementation with multiple nutrients (zinc, vitamin A, iron, copper, and vitamin C) from 2003 to 2009 was more effective in improving growth than vitamin A supplementation alone or combined only with zinc. Hieu et al 4 studied 381 school children in Vietnam and also found higher weight for stature (W/S) z-scores among those who received cookies fortified with multi-nutrients (iron, zinc, vitamin C, vitamin A, calcium and magnesium) for 6 months, compared to those who received a weekly iron supply of ferrous fumarate.…”
Section: Discussionmentioning
confidence: 99%
“…After a 6-month intervention period, the test group compared with the control showed higher weight and height gains, higher concentrations of hemoglobin, serum ferritin and retinol, and lower prevalence of iron deficiency anemia. Hieu et al 4 also observed lower prevalence of iron deficiency anemia in children receiving multinutrient-fortified cookies containing iron, zinc, vitamin A, vitamin C, calcium and magnesium (1%) when compared with the control group (10.4%). Those who received a weekly iron supplementation showed an intermediate prevalence of anemia (7.4%) after intervention.…”
Section: Nutrient Ear Prevalence Of Inadequacymentioning
confidence: 91%